Guide to the English school in international studies - Navari, Cornelia, 1941- (Chichester, West Sussex ; Malden, MA : Wiley Blackwell, 2014)
"Serves as an essential reference for students, researchers, and academics in international relations"--
Order and Justice TodayReferences; 10 The Pluralist-Solidarist Debate in the English School; Origins of Debate; Purpose, Procedure, and Humanitarian Intervention; Theorizing World Order; The Vocabulary of Debate; References; 11 Three Traditions of International Theory; Introduction; What Is "International Theory?"; The Role of the History of Ideas; Putting Past Thinking into Order; The Three Traditions; The Reception of the Three Traditions; Notes; References; 12 Normative Theory in the English School; Introduction; The British Committee and the Contours of the Middle Ground.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: International relations -- Philosophy; International relations; International relations -- Great Britain; POLITICAL SCIENCE -- International Relations -- General; International relations; International relations -- Philosophy; Electronic books